Serum folate receptor α (sFR) in ovarian cancer diagnosis and surveillance - Batoul Farran; Samet Albayrak; Judith Abrams; Michael A. Tainsky; Nancy K. Levin; Robert Morris; Larry H. Matherly; Manohar Ratnam; Ira Winer (Cancer Medicine)
Abstract Novelty and Impact Statement: Our findings suggest that soluble folate receptor (sFR) could be used in both the initial diagnosis and surveillance of patients with ovarian cancer. Our cohort constitutes one of the largest comparison groups for sFR analyzed so far. We have defined the background level of sFR using healthy volunteers. This is also the first study to prospectively follow patients in the surveillance setting to concurrently identify differential changes in tumor markers CA‐125 and sFR.